2012
DOI: 10.1371/journal.pone.0048160
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box M1 (FoxM1) Gene Is a New STAT3 Transcriptional Factor Target and Is Essential for Proliferation, Survival and DNA Repair of K562 Cell Line

Abstract: The forkhead box (Fox) M1 gene belongs to a superfamily of evolutionarily conserved transcriptional regulators that are involved in a wide range of biological processes, and its deregulation has been implicated in cancer survival, proliferation and chemotherapy resistance. However, the role of FoxM1, the signaling involved in its activation and its role in leukemia are poorly known. Here, we demonstrate by gene promoter analysis, Electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 43 publications
(49 reference statements)
2
41
0
Order By: Relevance
“…4F ). Consistent with this, FoxM1, which is known to regulate both G1/S and G2/M progression via several proteins, including cyclin D1, CDC25, AURAK, STMN1 and PLK1 (27), showed significantly reduced level in IB-treated breast cancer cells ( Figs. 4C and G ).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…4F ). Consistent with this, FoxM1, which is known to regulate both G1/S and G2/M progression via several proteins, including cyclin D1, CDC25, AURAK, STMN1 and PLK1 (27), showed significantly reduced level in IB-treated breast cancer cells ( Figs. 4C and G ).…”
Section: Resultssupporting
confidence: 72%
“…To begin to address the mechanism by which IB may regulate its targets, we focused on FoxM1 since several IB target genes including SKP2 (33), EXO1 (31), Rad51 (31), STMN1 (34) and AURKA (27) are reported to be transactivated by FoxM1. The dramatically reduced expression of FoxM1 in IB-treated breast cancer cells prompted us to test whether IB may directly interact with FoxM1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not due to alterations in the expression of the farnesoid X receptor (Fxr), a direct activator of the Foxm1 gene (figure 3F). However, levels of phosphorylated (activated) Stat3, a positive regulator of the Foxm1 gene,25 were much lower in Fgfr4 knockdown mice at 24 h after PH compared with controls, while the early Stat3 activation was not affected (figure 3G). This was not a consequence of interleukin (IL)-6 deficiency since serum levels of IL-6 and its upstream regulator tumour necrosis factor-α were even increased in mice with Fgfr4 knockdown at this time point (see online supplementary figure S4A,B).…”
Section: Resultsmentioning
confidence: 98%
“…8E). A recent report has shown that Foxm1 is the target of the STAT3 transcriptional activator in K562 cells (27). We found that the amounts of STAT3 and its phosphorylated L H 3 K 2 7 m e 3 H 3 K 2 7 m e 3 H 3 1 R L R R H 3 K 2 7 m e 3 H 3 K 2 7 m e 3 3 K 2 7 m e 3 2 7 m 2 7 2 2 R L H 3 K 2 7 m e 3 1 R L H 3 K 2 7 m e 3 2 S h a m H 3 K 2 7 m e 3 1 S h a m H 3 K 2 7 m e 3 m e form were increased in the regenerating liver (Fig.…”
Section: The Integration Of the Cistrome And The Transcriptome Pointsmentioning
confidence: 99%